Developing Atlas of Ficus Plant Morphology Based on Local Potency of Bantimurung Bulusaraung National Park as Botany Learning Material in the College - Ummul Hasanah; Murni Saptasari; Dahlia Dahlia (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2022)
Learning based on local potential is a curriculum demand contained in the National Standards of Higher Education. One of the local potentials in the South Sulawesi region is Bantimurung Bulusaraung National Park with high biodiversity. There are 709 species of plants and among them, there are 43 types of Ficus plants that are key species in the area. This research aims to develop a plant morphology atlas based on the local potential of Bantimurung Bulusaraung National Park as botanical teaching materials in universities. Development adapts the stages of the ADDIE model. Research data in the form of qualitative data and quantitative data obtained from material experts, teaching materials development experts, education practitioners, and learners. The data obtained is then analyzed using the validity percentage formula. The validation of products with a value of 97.6% indicates that the plant morphology atlas of material aspects includes valid criteria. The taught material development apex obtained a value of 99.6% which indicates a very valid criterion. Based on the results of validation from education practitioners which is 76.7% and includes quite valid criteria. The results of the trial in a small group obtained a value of 84% with excellent validity. In conclusion, the atlas developed valid and practice as teaching material. So, this atlas can be used as a teaching material for supplements, especially in plant morphology courses in universities.